Measuring Design-DK and True Permittivity of PCB Materials up to 20 GHz - Gold, Gerald; Helmreich, Klaus (Proceedings of the 9th German Microwave Conference (GeMiC2015), 2015)
Many measurement methods for dielectric properties are influenced by surrounding conductor structures, which is especially significant in the case of copper cladded PCB materials. The paper explains the reasons for this, shows how to interpret data sheet values and introduces a measurement assembly and method that allows for precise determination of true relative permittivity and loss tangent. The presented assembly is customized for thin PCB material.
UnivIS-Import:2015-10-26:Pub.2015.tech.IE.c3scha.measur